Financial needs and the prospects of digital financial services in the agricultural midstream: Phase 1 synthesis - Ambler, Kate; de Brauw, Alan; Herskowitz, Sylvan; Pulido, Cristhian (International Food Policy Research Institute, 2022)
Agricultural commodity value chains (AVCs) are critical for providing income to farmers, creating em ployment opportunities, generating export revenue, and providing affordable and healthy food for con sumers. Agriculture employs 42% of people in South Asia and 53% in sub-Saharan Africa (World Bank, 2022), while agricultural growth has been shown to be three times more effective at poverty reduction than growth in other sectors (de Janvry and Sadoulet, 2009). Though the majority of existing literature has focused on producers and consumers, recent research suggests that value added in the “mid stream” of value chains, the actors between farmgate and final vendors, may be as large as 40% of the total gross value in the agricultural sector (Reardon, 2015; AGRA, 2019). This midstream is comprised predominantly of small and medium size enterprises (SMEs) including traders, transporters, and processors whose potential for growth may be considerably untapped.In general, the high seasonality, geographic dispersion, and unpredictable output of the agricultural sector can make it especially difficult for the financial needs of the midstream to be met, challenges well documented and studied among small-scale producers. While there has been recent, increasing atten tion on the midstream actors in AVCs, focus on their financial needs is rare. If, in fact, they lack much access to financial products, an increase in access could lead to increased employment opportunities in the midstream, as well as more robust growth. Additionally, recent years have seen the emergence of a number of digital financial services (DFS), including mobile money and digital payment systems, digital credit, and digital marketplaces, all of which hold potential for alleviating meaningful constraints among midstream actors in AVCs. The aim of this project was to take stock of what is known about these midstream AVC actors, their fi nancial needs, and the potential of DFS to help meet those needs. In this synthesis, we summarize les sons from the project’s first phase, which included a literature review, analysis of existing microdata, documentation of previous data targeted at the midstream, and interviews with other experts in the field.